Efektivitas Modul Pembelajaran Tematik Berbasis Model RADEC Pada Subtema “Manfaat Energi” Untuk Kelas IV Sekolah Dasar - Ika Dwi Lestari (Universitas Negeri Makassar, 2022)
One of the innovations in teaching materials in elementary schools is the learning module. The integrative thematic learning module innovation is needed to help students understand learning materials, build knowledge, and develop abilities. This study aims to determine the effectiveness of the integrative thematic learning module based on the RADEC (Read-Answer-Discuss-Explain-Create) model on the “Manfaat Energi” sub-theme. The subjects in this study were fourth-grade elementary school students. This study uses quantitative methods. The results of the effectiveness test were obtained through Pretest and Posttest to determine the effect of implementing learning modules on improving learning outcomes. The results showed that the average pretest results obtained a percentage of 72% and the average posttest results obtained a percentage of 83%. Based on these results, there is an increase in student learning outcomes by 11%. The effectiveness of this learning module is supported by various aspects that are emphasized in the module, including aspects of material/content, presentation, language, and graphics. These four aspects are integrated in such a way that they can help students develop their communication and creation skills. It can be concluded that, there is an increase in learning outcomes for fourth-grade elementary school students after the implementation of the thematic integrative learning module based on the RADEC (Read-Answer-Discuss-Explain-Create) sub-theme on